Equity in opportunity-to-learn and achievement in reading: A secondary analysis of PISA 2009 data. (December 2015) - Lafontaine, Dominique; Baye, A.; Vieluf, S.; Monseur, C.
Highlights: Among 15 year-olds, students' exposure to OTL in reading varies from school to school. The variation per school of OTL is stronger in differentiated education systems than in comprehensive ones. Differential exposure to OTL is correlated with the socioeconomic composition of the school. Robust correlations between the dimensions of OTL in reading and achievement are observed. Abstract: Using data from PISA 2009, the present study investigates firstly how equally students are exposed to opportunities to improve their reading skills (OTL) depending on the school they are enrolled in, and secondly the links between OTL in reading and achievement at the school level. A multidimensional within-item IRT is used to model the OTL. The intraclass correlation of both OTL dimensions issued from the IRT analysis – reading fiction and reading non-continuous tasks – is high, especially in differentiated education systems, showing an unequal exposure to OTL in reading according to the school. Robust correlations between the two OTL dimensions and reading achievement are observed at the school level. In addition, the results of a multilevel regression analysis show that a substantial proportion of the between-school variance in reading can be explained by OTL and by the school social intake. The proportion of between-school variance explained jointly by OTL and social intake is higher in differentiated education systems than in comprehensive ones.